Anesthetic implications in patients with myasthenia gravis undergoing spine surgery - Bhanupreet Kaur; Gurpreet Singh; Haramritpal Kaur; Inderpreet Singh (Indian Journal of Case Reports, 2021)
Myasthenia gravis is a chronic autoimmune disorder affecting post-synaptic neuromuscular junction. It is characterized by skeletal muscle weakness and fatigability which improves with rest. The anesthesiologists may encounter these patients for thymectomy or sometimes for incidental surgeries. However, it is a real challenge for anesthesiologists because of the unpredictable response with muscle relaxants and analgesics and the possibility of ventilatory complications. In the present case report, we report the management of a 52-year-old female patient with myasthenia gravis who is posted for schwannoma surgery.